Cell therapy for neurological disorders: Progress towards an embryonic medial ganglionic eminence progenitor-based treatment - Righes Marafiga, Joseane; Baraban, Scott C. (Frontiers in Neuroscience, 2023)
Impairment of development, migration, or function of inhibitory interneurons are key features of numerous circuit-based neurological disorders, such as epilepsy. From a therapeutic perspective, symptomatic treatment of these disorders often relies upon drugs or deep brain stimulation approaches to provide a general enhancement of GABA-mediated inhibition. A more effective strategy to target these pathological circuits and potentially provide true disease-modifying therapy, would be to selectively add new inhibitory interneurons into these circuits. One such strategy, using embryonic medial ganglionic (MGE) progenitor cells as a source of a unique sub-population of interneurons, has already proven effective as a cell transplantation therapy in a variety of preclinical models of neurological disorders, especially in mouse models of acquired epilepsy. Here we will discuss the evolution of this interneuron-based transplantation therapy, with an emphasis on the recent adaptation of MGE progenitor cells for xenotransplantation into larger mammals